Dispute Resolution of Problem Financing in Indonesian Islamic Banks by Basyarnas - Oktaviany, Mega; Muhammad Alif Ramadhan; Rizkina Zakaria (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2024)
Purpose: This study discusses whether there is a dispute, and whether Indonesian positive law has usually provided a way for both parties to resolve it. The process that parties can undertake can be either extrajudicial proceedings or court proceedings (litigation). Method: This research applies a literature review. We collected information on regulations, research, books, documents, records, websites, and various other literature related to BASYARNAS regarding dispute resolution in Islamic banking. The secondary data used in the analysis included data from Law No. 30/1999, Indonesian Banking Surveillance Report-Third Quarter 2023, and data from the National Sharia Arbitration Board of Indonesia. Results: The results show that the role of BASYARNAS is not yet ideal because it must be preceded by written consent from the parties, and the overlapping jurisdiction between religious courts and district courts hinders the enforcement of arbitration awards. Limitations: This research suggests the need for stricter regulations regarding the jurisdiction of Islamic bank financing disputes to avoid jurisdictional dualism. There is a need for a legal infrastructure that supports Sharia-based businesses by providing effective and culturally relevant out-of-court dispute resolution mechanisms with the principles and values of Sharia commerce. Contribution: Arbitration is considered by entrepreneurs as the best way to resolve disputes out of court, as it suits the needs of businesses.